2019
DOI: 10.1136/bmjopen-2018-025967
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported health problems and obesity predict sickness absence during a 12-month follow-up: a prospective cohort study in 21 608 employees from different industries

Abstract: ObjectivesTo study whether self-reported health problems predict sickness absence (SA) from work in employees from different industries.MethodsThe results of a health risk appraisal (HRA) were combined with archival data of SA of 21 608 employees (59% female, 56% clerical). Exposure variables were self-reported health problems, labelled as ‘work disability (WD) risk factors’ in the HRA, presence of problems with occupational well-being and obesity. Age, socioeconomic grading and the number of SA days 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Similar to SA [ 1 2 3 4 ], SP was associated with the poor health status of employees because it indicates the possibility of worker ill-health [ 11 41 ]. Moreover, SP could contribute to the spread of communicable diseases, such as common cold or influenza, in the workplace, and eventually to the general population [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to SA [ 1 2 3 4 ], SP was associated with the poor health status of employees because it indicates the possibility of worker ill-health [ 11 41 ]. Moreover, SP could contribute to the spread of communicable diseases, such as common cold or influenza, in the workplace, and eventually to the general population [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…SA has been extensively studied because it can increase social costs due to employee health problems and their reduced productivity [ 1 2 3 4 ]. In contrast, the importance and seriousness of SP has only recently been explored, particularly in Korea [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 Sickness absenteeism is defined as the time absent from work because of illness. 19 Fitzgerald et al 14 confirmed that obesity is recognised as a significant predictor of sick leave and it has been shown that obese workers experienced higher rates of sickness absenteeism, 20,21 and presenteeism. 5 Even though obesity has been associated with significantly greater absenteeism among United States (US) workers, after controlling for demographic characteristics, 5 the causes of workplace absenteeism are multifaceted and not limited to obesity and health status outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, due to its simplicity and low cost in obtaining health information from individuals, self-reporting has become an integral approach for continuous population monitoring, informing policies aimed at reducing the burden of various diseases [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Self-reporting of specific medical conditions is a simple and cost-effective method that relies on individuals willingly disclosing their behaviors, beliefs, attitudes, or intentions regarding a particular condition. Therefore, due to its simplicity and low cost in obtaining health information from individuals, self-reporting has become an integral approach for continuous population monitoring, informing policies aimed at reducing the burden of various diseases [18, 19].…”
Section: Introductionmentioning
confidence: 99%